Different genetic components in the Ethiopian population, identified by mtDNA and Y-chromosome polymorphisms. - Passarino, G (1998)
Seventy-seven Ethiopians were investigated for mtDNA and Y chromosome-specific variations, in order to (1) define the different maternal and paternal components of the Ethiopian gene pool, (2) infer the origins of these maternal and paternal lineages and estimate their relative contributions, and (3) obtain information about ancient populations living in Ethiopia. The mtDNA was studied for the RFLPs relative to the six classical enzymes (HpaI, BamHI, HaeII, MspI, AvaII, and HincII) that identify the African haplogroup L and the Caucasoid haplogroups I and T. The sample was also examined at restriction sites that define the other Caucasoid haplogroups (H, U, V, W, X, J, and K) and for the simultaneous presence of the DdeI10394 and AluI10397 sites, which defines the Asian haplogroup M. Four polymorphic systems were examined on the Y chromosome: the TaqI/12f2 and the 49a,f RFLPs, the Y Alu polymorphic element (DYS287), and the sY81-A/G (DYS271) polymorphism. For comparison, the last two Y polymorphisms were also examined in 87 Senegalese previously classified for the two TaqI RFLPs. Results from these markers led to the hypothesis that the Ethiopian population (1) experienced Caucasoid gene flow mainly through males, (2) contains African components ascribable to Bantu migrations and to an in situ differentiation process from an ancestral African gene pool, and (3) exhibits some Y-chromosome affinities with the Tsumkwe San (a very ancient African group). Our finding of a high (20%) frequency of the "Asian" DdeI10394AluI10397 (++) mtDNA haplotype in Ethiopia is discussed in terms of the "out of Africa" model.